Timing of surgery following SARS‐CoV‐2 infection: an international prospective cohort study - Gacaferi, H; COVIDSurg Collaborative; GlobalSurg Collaborative (Wiley, 2021)
Peri‐operative SARS‐CoV‐2 infection increases postoperative mortality. The aim of this study was to determine the optimal duration of planned delay before surgery in patients who have had SARS‐CoV‐2 infection. This international, multicentre, prospective cohort study included patients undergoing elective or emergency surgery during October 2020. Surgical patients with pre‐operative SARS‐CoV‐2 infection were compared with those without previous SARS‐CoV‐2 infection. The primary outcome measure was 30‐day postoperative mortality. Logistic regression models were used to calculate adjusted 30‐day mortality rates stratified by time from diagnosis of SARS‐CoV‐2 infection to surgery. Among 140,231 patients (116 countries), 3127 patients (2.2%) had a pre‐operative SARS‐CoV‐2 diagnosis. Adjusted 30‐day mortality in patients without SARS‐CoV‐2 infection was 1.5% (95%CI 1.4–1.5). In patients with a pre‐operative SARS‐CoV‐2 diagnosis, mortality was increased in patients having surgery within 0–2 weeks, 3–4 weeks and 5–6 weeks of the diagnosis (odds ratio (95%CI) 4.1 (3.3–4.8), 3.9 (2.6–5.1) and 3.6 (2.0–5.2), respectively). Surgery performed ≥ 7 weeks after SARS‐CoV‐2 diagnosis was associated with a similar mortality risk to baseline (odds ratio (95%CI) 1.5 (0.9–2.1)). After a ≥ 7 week delay in undertaking surgery following SARS‐CoV‐2 infection, patients with ongoing symptoms had a higher mortality than patients whose symptoms had resolved or who had been asymptomatic (6.0% (95%CI 3.2–8.7) vs. 2.4% (95%CI 1.4–3.4) vs. 1.3% (95%CI 0.6–2.0), respectively). Where possible, surgery should be delayed for at least 7 weeks following SARS‐CoV‐2 infection. Patients with ongoing symptoms ≥ 7 weeks from diagnosis may benefit from further delay.